2019
DOI: 10.2174/1389201020666190808154341
|View full text |Cite
|
Sign up to set email alerts
|

Changes in the Density of Corneal Endothelial Cells in Elderly Diabetic Patients After Combined Phacovitrectomy and Ex-PRESS Glaucoma Implants

Abstract: Background & Objective: Corneal endothelial cells (ECD) are characterized by limited regenerative potential, which is additionally impaired in patients with diabetes. This retrospective study included 27 patients aged 58.1±13.6, 16 female and 11 males, who underwent 23-gauge vitrectomy in combination with cataract surgery (phacovitrectomy) and further Ex-PRESS shunt implantation throughout 2013-2017 at St. Barbara Hospital in Sosnowiec, Poland. Methods: In our study, we distinguished 4 periods: initial p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
4
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 39 publications
0
4
0
Order By: Relevance
“…It was suggested that the reduction of ECD was greater in tube-shunt surgery than in trabeculectomy 17. In addition, Ex-PRESS shunt implantation was associated with a significant reduction in the number of corneal endothelial cells, despite the reduction was found to be lower than that observed after classical trabeculectomy 20,21…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…It was suggested that the reduction of ECD was greater in tube-shunt surgery than in trabeculectomy 17. In addition, Ex-PRESS shunt implantation was associated with a significant reduction in the number of corneal endothelial cells, despite the reduction was found to be lower than that observed after classical trabeculectomy 20,21…”
mentioning
confidence: 99%
“…in the number of corneal endothelial cells, despite the reduction was found to be lower than that observed after classical trabeculectomy. 20,21 Minimally invasive glaucoma surgery may offer a safer and less invasive means of lowering intraocular pressure (IOP) than traditional surgery. 22,23 However, it should be noted that the supraciliary CyPass micro-stent has been withdrawn from the market after the results of the COMPASS-XT long-term safety study, which reported a significant ECD reduction in patients undergoing the implantation of the micro-stent in combination with cataract surgery.…”
mentioning
confidence: 99%
“…Since cornea endothelial cells from feline species have no proliferation (Landshman et al, 1987), they are considered similar to HCECs, which thus provide a great model to assess the cytotoxicity of carteolol. Our results showed that 2% clinical carteolol induces a time-dependent reduction in corneal ECD, and increases the average size ratio of endothelial cells in vivo, which can cause deterioration in visual acuity in ophthalmic disease (Lyssek-Boroń et al, 2019). Furthermore, ultrastructural observations showed that FCE cells had shrunk, and this process was accompanied by mitochondrial swelling and cytoplasmic vacuolation after carteolol treatment .…”
Section: Discussionmentioning
confidence: 64%
“…Our results coincide with theirs. 16,17 Hugod M. et al noted that patients with diabetes had a lengthy recovery period from corneal edoema and significant CED destruction. The mean CED depletion was found to be 6.2% in the diabetic group and 1.4% in the control category after the researchers evaluated 30 patients with type 2 diabetes and 30 healthy subjects.…”
Section: Discussionmentioning
confidence: 99%